Highly Efficient and Recyclable Catalysts for Cellobiose Hydrolysis: Systematic Comparison of Carbon Nanomaterials Functionalized With Benzyl Sulfonic Acids - Carlier, Samuel; Hermans, Sophie (Frontiers in Chemistry, 2020)
Carbon materials such as activated coal, nanotubes, nanofibers, or graphene nanoplatelets were functionalized with sulfonic acid moieties by a diazonium coupling strategy. High acidity was obtained for the majority of the carbon solids except for the carbon nanofibers. The activity of these acidic catalysts for the hydrolysis of cellobiose, as model molecule for cellulose, into glucose in neutral water medium was studied. The conversion of cellobiose is increasing with the acidity of the catalyst. We found that a minimum threshold amount of acidic functions is required for triggering the hydrolysis. The selectivity toward glucose is very high as soon as sulfonic functions are present on the catalyst. The robustness of the sulfonic functions grafted on the carbons has been highlighted by successful recyclability over six runs.